Assessing the Consistency of Two Models of Benzene Neurotoxicity Risk Assessment to Create and Validate a Health Risk Screening Guideline Among Fuel Service Workers - Anamai Thetkathuek; Polyong, Chan Pattama (International Journal of Occupational Safety and Health, 2025)
Introduction: This research and development study aimed to (1) evaluate the consistency of two models of benzene neurotoxicity risk assessment (NRA) and (2) create and validate a neurotoxicity risk screening manual among fuel service workers (FSW). Data were collected through interviews and urine collection. The neurotoxicity risk screening was divided into two models: qualitative neurotoxicity risk assessment (NRA-1) and quantitative neurotoxicity risk assessment (NRA-2). The two sample groups included inside- and outside the fuel dispenser area were 100 per group, and a neurotoxicity risk screening guide was created and validated using a panel of 15 experts. Methods: NRA-1 used the following variables in health screening to assess exposure to benzene: frequency of exposure, duration of work (years), number of working hours, number of overtime hours per week, number of trucks providing refueling services per day, and reuse of clothes. NRA-2 used two variables to screen for frequency of exposure: frequency of work (hours per day) and trans, trans-muconic acid (t,t-MA) levels in urine. Results: NRA-1 showed that 29.0% of the workers had a low risk level, 37.0% moderate, 13.0% high, and 2.0% very high. For NRA-2, 32.0% of the workers had a low risk level, 37.5% moderate, 11.5% high, and 6.0% very high. Both NRAs were statistically significantly consistent (r = 0.409, p < 0.001). The neurotoxicity risk screening guide was criticized by experts, and it can be concluded that it can be used as a pilot for neurotoxicity screening of FSWs. Conclusion: The risk assessment was conducted using both qualitative (NRA-1 model) and quantitative (NRA-2 model) methods. Both methods can be applied to easily implement the assessment. The low-cost method can be used to perform the qualitative assessment without testing for metabolites in urine.